(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: Maternal bearing down efforts plays a vital role in expulsive phase of labor. Various types of bearing down efforts has got its own advantages and disadvantages on mother and fetus. Various studies are done to evaluate the best bearing down techniques and have different results .The investigator personally felt there is a need to investigate the best bearing down technique with less complications to the mother and newborn Objective: 1.To assess the effect of vulsalva bearing down technique during second stage of labour on maternal and neonatal outcome among primigravida mothers admitted in selected hospitals of pune city. 2.To assess the effect of spontaneous bearing down technique during second stage of labour on maternal and neonatal outcome among primigravida mothers admitted in selected hospitals of pune city.3.To compare the effectiveness of vulsalva bearing down techniques and spontaneous techniques and duration of second stage of labour on maternal and neonatal outcome among primigravida mothers admitted in selected hospitals of pune city Methodology: In the present study, Quantitative research approach is applied and approach is applied and pre experimental ,Post test only control group design is used. The setting of the study was selected hospital of Pune. The sample size for study was 60, selected by using Non Probability Purposive Sampling Technique. The structured questionnaire and observation checklist was administered. In order to establish the reliability of the tool inter rater method was used. The scores were calculated and the reliability was established by Kappa method, which was 0.90. Results: On Comparison of the Spontaneous and vulsulva bearing down techniques on various maternal and neonatal outcome. Since the P values corresponding to the Maternal outcome, oxytocin given, Perineal laceration ,Type of episiotomy, size of episiotomy ,mode of delivery and fatigue and Neonatal outcome Crown heel length of newborn ,Head circumference of newborn, Neonate Resuscitation, Admission to NICU,APGAR score are small (less than 0.005) suggests that vulsulva bearing down technique is significantly different that spontaneous bearing down technique in the above maternal and neonatal outcomes and good result for the health of mother and newborn Conclusion: The Spontaneous pushing method has a negative effect on various factors related to maternal and neonatal outcome factors according to the results in this study. Vulsalva pushing has various benefits towards the better health of Mother and Newborn so it should be accepted as best clinical practice